STRES BEBAN KERJA DAN TANGGUNG JAWAB POLISI: TINJAUAN LITERATUR - Divania Fazrina; Didik Irawan, Wustari L. Mangundjaya (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Background: A police officer is someone with a high responsibility for protecting the safety and security of the community and reducing crime rates. Police work in dealing with crime is very dangerous and full of risks, and often with unpredictable threats. To overcome this, the police set tough targets with high discipline and focus, which requires constant preparedness. Consequently, this condition causes stress at work. Method: This article used a method of a literature review. Researchers searched for articles using the Bold database via Google Scholar. The keywords used are "police workload stress", and "police responsibility". The criteria for selected articles include complete articles (full text), can be accessed freely (open access), and a SINTA-indexed journal. The selected journals are limited from the last 4 (four) years. Results: The results of literature review were found that factors which influenced the workload stress and police responsibilities, namely: workload, work environment, and job shifts. Those factors play a significant role in the level of stress experienced by a police. Additionally, it also showed that there is a need of supports and stress management strategies in the police work environment. Conclusion: Various factors influence the stress of a police workload and responsibilities. Therefore, to enhance employee productivity and well-being, the police organization need to develop and implement programs that can help manage and reduce stress. Coaching and counselling program combined with the opportunity and facilities for entertainment and exercises are recommended for redusing stress.